2011
DOI: 10.1111/j.1600-0846.2011.00554.x
|View full text |Cite
|
Sign up to set email alerts
|

Skin hydration and cooling effect produced by the Voltaren® vehicle gel

Abstract: This study showed a statistically significant increase in skin hydration as well as a rapid cooling effect lasting approximately 30 min, after application of Voltaren vehicle gel. The small relative increase in water loss may be attributed to an additional skin surface water loss secondary to the increased water content brought into the skin by the Voltaren vehicle gel. The use did not induce any skin irritation and was found acceptable to use by the majority of participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…measured skin temperature after 20 min of 40% menthol ointment application and found that menthol did not have any significant effect to skin temperature. Furthermore, Voltaren ® vehicle gel, which does not have menthol, seems to have quite similar cooling properties as the gels tested in this study. For Voltaren ® gel, average temperature drop was 5.1°C, whilst for menthol gels tested in this study median temperature drop was 5.7°C (10.0% gel), 6.2°C (0.5% gel), 5.7°C (4.6% gel).…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…measured skin temperature after 20 min of 40% menthol ointment application and found that menthol did not have any significant effect to skin temperature. Furthermore, Voltaren ® vehicle gel, which does not have menthol, seems to have quite similar cooling properties as the gels tested in this study. For Voltaren ® gel, average temperature drop was 5.1°C, whilst for menthol gels tested in this study median temperature drop was 5.7°C (10.0% gel), 6.2°C (0.5% gel), 5.7°C (4.6% gel).…”
Section: Discussionmentioning
confidence: 50%
“…In these studies, ultrasound was used to measure menthol's effect to blood flow. Modern infrared thermal (IRT) imaging, providing good image and thermal resolution, is a potential method for detecting changes in skin temperature , e.g. due to variation in blood flow.…”
mentioning
confidence: 99%
“…All measurements and procedures in this study were performed in a climate-controlled room at a constant temperature and humidity (23°C and 60% relative humidity) [32]. Before assessment, participants were required to lie down in the aforementioned room for 30 minutes to acclimatize to the indoor climatic conditions.…”
Section: Methodsmentioning
confidence: 99%
“…All measurements and procedures in this study were performed in a climate-controlled room at a constant temperature and humidity (23 • C and 60% relative humidity). Before assessment, participants were required to lie down in this room to acclimatize to these indoor climatic conditions for 30 minutes [14]. Participants were thermographed for the abdominal region by the Fluke Ti25 (Fluke Corporation, Everett, WA, USA).…”
Section: Measurementsmentioning
confidence: 99%